Effect of Low Versus High-Heeled Footwear on Spinopelvic Alignment at Different Phases of Menstrual Cycle in Young Adult Women: A Biopsychosocial Perspective - El-Shafei, Manal A.; Yousef, Amel M.; Hamada, Hamada A.; Mohamed, Mohamed F.; Al-Shenqiti, Abdullah M.; Koura, Ghada M. R.; López Sánchez, Guillermo F. (Frontiers in Psychology, 2021)
High-heeled shoes adversely affect spinal curvature, increase the risk of low back pain, and disturb the normal gait pattern. The purpose of this study was to examine, from a biopsychosocial point of view, the combined effect of wearing two different heel heights and of hormonal oscillation throughout different phases of the menstrual cycle on spinopelvic alignment. Notably, 70 females with an average age of 20.42 ± 1.51 years participated in this study, wearing each female two different heel heights as follows: low (2.5 cm) and high (7 cm). Spinopelvic alignment was evaluated by rasterstereography formetric 3D analysis during early follicular, ovulatory, and mid-luteal phases of the menstrual cycle. Statistical analysis showed that there was no significant difference (p > 0.05) on spinopelvic alignment [kyphotic angle (KA), trunk inclination (TI), and pelvic inclination] between wearing low- or high-heeled shoes during early follicular, ovulatory, and mid-luteal phases of the menstrual cycle. Considering that high-heeled shoes are traditionally associated with femininity, body image, beauty, and charm, this research has important biopsychosocial implications that should be explored in detail in future studies.